The Effect of Ownership Structure on Firm Value With Debt Policy As Intervening Variable (Study on LQ45 Companies on the Indonesian Stock Exchange) - ZULFAN EPENDI (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to determine and analyze the effect of ownership structure and debt policy on firm value. Effect of ownership structure on firm value with debt policy as an intervening variable. The population in this study were LQ45 companies in the form of financial reports downloaded from www.idx.co.id, namely 45 companies. then the companies studied were lq45 companies as many as 27 companies. The analytical method used is path analysis. The results of this study indicate that ownership structure affects firm value. Furthermore, ownership structure influences firm value with debt policy as an intervening variable. ownership structure does not affect debt policy. Debt policy does not affect the value of the company.